From sequencamers to foldamers? Tetrameric furanose carbopeptoids from cis- and trans-5-aminomethyl-tetrahydrofuran-2-carboxylates - Long, D; Hungerford, N; Smith, M; Brittain, D; Marquess, D; Claridge, T; Fleet, G (1999)
The synthesis of three stereoisomeric cis- and trans-5-azidomethyl- tetrahydrofuran-2-carboxylates in which a ketal-protected cis-diol unit is present is described. The monomers undergo efficient oligomerisation to tetrameric carbopeptoids in which the diol protection facilitates ready purification by chromatography which augurs well for the formation of homogeneous higher polymers.